2010
DOI: 10.1002/adfm.201001140
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Assembly of Bridged β‐Ga2O3 Nanowires for Solar‐Blind Photodetection

Abstract: An increasing number of applications using ultraviolet radiation have renewed interest in ultraviolet photodetector research. Particularly, solar‐blind photodetectors sensitive to only deep UV (<280 nm), have attracted growing attention because of their wide applicability. Among recent advances in UV detection, nanowire (NW)‐based photodetectors seem promising, however, none of the reported devices possesses the required attributes for practical solar‐blind photodetection, namely, an efficient fabrication proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
220
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(230 citation statements)
references
References 41 publications
9
220
1
Order By: Relevance
“…In recent years, this technique has been used to fabricate bridging nanowire devices such as gas sensors, photodetectors, and transistors with Si, GaN, and ZnO. [96][97][98][99][100][101][102][103][104][105][106][107] The bridging method which was first demonstrated by Haraguchi et al 96 by growing GaAs nanowires means that the wires can be laterally grown across a trench between two electrode posts which were already etched on a substrate. The schematic diagrams are shown in Fig.…”
Section: Assembly By Bridging Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, this technique has been used to fabricate bridging nanowire devices such as gas sensors, photodetectors, and transistors with Si, GaN, and ZnO. [96][97][98][99][100][101][102][103][104][105][106][107] The bridging method which was first demonstrated by Haraguchi et al 96 by growing GaAs nanowires means that the wires can be laterally grown across a trench between two electrode posts which were already etched on a substrate. The schematic diagrams are shown in Fig.…”
Section: Assembly By Bridging Methodsmentioning
confidence: 99%
“…These nanowire devices can be used as gas sensors, photodetectors, and transistors. [104][105][106] Particularly, Kim et al 107 demonstrated that this method could be used to directly grow Si nanowire-based AND and OR diode logic gates with excellent rectifying behaviors, and photovoltaic elements in parallel in series, with tunable power output.…”
Section: Assembly By Bridging Methodsmentioning
confidence: 99%
“…For this reason, important results have recently been obtained in the eld of optoelectronic solar-blind 'active' transducers by means of Ga-oxide nanowire assemblies. 8 Instead, the production of crystalline Ga-oxide as optical quality macroscopic components for 'passive' UV-to-visible windows is too expensive to be competitive with devices employing UV-sensitive or intensied detectors, even though quite complex and expensive. At present, the lack of low-cost alternative solutions for simultaneous UV and visible imaging prevents us from monitoring on a large-scale a wide variety of UV-emitting invisible events, which can affect human safety conditions in working places, energy-saving, and electric power distribution reliability, such as hydrogen ames, electric sparks, and corona dispersions in high-voltage lines.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we also show how the population of intrinsic acceptor and donor sites can be controlled by selective doping. In this way, UV and blue emissions can be optimized for different purposes, including solar-blind UV-to-blue converters 8,9 and UV-emitting devices. 27 …”
Section: Introductionmentioning
confidence: 99%
“…The effect of these parameters on the properties of the device can be studied by optical or electrical methods as the correlation between luminescence and electrical properties in β-Ga 2 O 3 has already been reported. 7,[22][23][24] From our previous studies, it is clear that in β-Ga 2 O 3 nanostructures, UV band intensity is more prone to be affected by surface state trapping centers as compared to blue luminescence. 7,8 This is because, the photo excited electrons which give the UV luminescence, are mobile in the conduction band and get trapped at the surface states.…”
Section: Introductionmentioning
confidence: 97%